Production aspects of intensification and milk market quality in Amhara region, Ethiopia - Addisu, B.; Mesfin, B.; Mekonnen, Kindu; Duncan, Alan J. (2012)
The study was carried out in June 2010 in selected villages of Amhara region of Ethiopia, representing three levels of market quality (high, medium and low), with the general objective of developing a systematic understanding of the links between market opportunities and productivity increases in livestock, with a focus on dairy production. The present report focuses on production aspects of dairy intensification in Amhara region. Findings showed that feeding of concentrates for dairy cattle was more prominent in high market quality sites compared to medium and low market quality sites, which indicated the level of feed intensification as the market quality improved. The contribution of grazing to total diet was higher for indigenous than crossbred cows. Indigenous cows were allowed to graze freely throughout the year and were expected to meet their feed requirement from grazing, especially in the wet and harvest (crop aftermath grazing) seasons, and supplemented during the dry season when the condition of grazing pasture deteriorated. Crossbred cows that demanded better nutrition for better milk production were only allowed to graze for a limited number of hours in a day when grazing pasture was in better condition. They were mostly kept indoors during the dry season to meet their feed requirements through stall feeding. The proportion of crossbred cows exceeded that of indigenous cows in high market quality sites but the reverse applied in medium and low market quality sites. Milk yield data indicated that there is room for increasing average productivity by improving management practices. Due consideration should be given to alleviate the problems in reproductive and milk yield performance to increase productivity and improve dairy-derived income.